Pelaksanaan Knowledge Management dalam Tata Kelola Jurnal Pustaka Ilmiah Universitas Sebelas Maret Surakarta - Sri Junandi; Haryanto Haryanto (Pustabiblia: Journal of Library and Information Science, 2021)
This study aims to: describe the practice of implementing knowledge management in the management of the Jurnal Pustaka Ilmiah Journal, and to find out what activities are oriented towards increasing the culture of sharing knowledge in the management of the Jurnal Pustaka Ilmiah Journal. This research is a descriptive qualitative research. Data collection was carried out using interview, observation and documentation methods. The informants in this study were the managers of the current and previous Jurnal Pustaka Ilmiah Journal, amounting to 4 people. The data presented in a narrative format and equipped with supporting pictures in several parts. The findings of this study are that Jurnal Pustaka Ilmiah Journal’s human resources was still very limited, but have a strong commitment. Jurnal Pustaka Ilmiah Journal was led by an egalitarian leadership style. Communication between managers is carried out over various media both synchronously and asynchronously. Institutions play a role in providing material-immaterial support in this matter even though the intensity is still limited to ceremonial. Meanwhile, the learning process in managing Jurnal Pustaka Ilmiah Journal found that managers did not hesitate to try new things to improve the quality of journal management. The success of the knowledge transfer process is not the success of the journal manager alone, but rather needs to get support from various elements, such as the participation of parent institutions which is not limited to ceremonial to create a strong and professional management. This will have implications for increasing the confidence of readers and writers in Jurnal Pustaka Ilmiah as a credible reference in the field of library and information sciences.